(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
The study tries to explore the relationship between perceived organizational support and psychological empowerment with job performance. Further, it has also examined the mediating effect of organizational justice in the study. Sample for the study was collected from educationist working in higher educational institutions. Total 325 sample was used to study the relationship among study variables. Analysis of the study was done using IBM SPSS and AMOS software version 22. The findings of the study suggest that except one construct (i.e. meaning) of psychological empowerment rest all (i.e. competence, self-determination and impact) have significant influence on job performance. Whereas perceived organizational support is found related with job performance. The mediating effect of organizational justice is found between POS and JP whereas it partially mediates between PE and JP. The study is unique which tries to understand the relationship of study variables in context of higher educational institutions in India.